478 VENTRICULAR AND ATRIAL REMODELING AFTER EDGE-TO-EDGE TRANS-CATHETER MITRAL VALVE REPAIR: A PILOT STUDY. (15th December 2022) - Albini, Alessandro; Passiatore, Matteo; Leo, Giulio; Imberti, Jacopo Francesco; Valenti, Anna Chiara; Coppi, Francesca; Sgura, Fabio Alfredo; Boriani, Giuseppe
Abstract: Background: Percutaneous mitral valve repair (PMVR) is an established therapy for mitral regurgitation (MR) in patients at high risk for surgical treatment. The aim of this study was to determine the impact of PMVR on left and right ventricular (LV, RV) and left and right atrial (LA, RA) remodelling according to the mechanism of MR and history of atrial fibrillation (AF). Methods and results: Twenty-four patients (mean age 78.54 years ± 7.64 SD; 62.5% males) undergoing PMVR at our centre were prospectively enrolled. All the patients underwent echocardiography 1.6 ± 0.9 months before the procedure and after 5.7 ± 3.5 months; functional MR accounted for 54% of cases. Compared to baseline, a statistically significant improvement in LV end-diastolic diameter (LVEDD), LV indexed mass (ILVM), LV end-diastolic and end-systolic volumes (LVEDV, LVESV), indexed LA volume (iLAV) and morpho-functional RV parameters was recorded. LVEDD and LVEDV improved in primary MR cohort whereas in secondary MR a significant reduction in LVEDV and LVESV with a nonsignificant improvement in ejection fraction were found. (Table 1) LA positive remodelling was found in organic MR with a trend toward ameliorated function; in functional MR, with more dilated and dysfunctional LA, no significant improvement was found. (Table 1) Furthermore, a significant reduction of LA volumetry was detected only in patients without history of AF (AF baseline 51.4 mL/m2 IQR 45.6-62.5 mL/m2 f-u 48.9 mL/m2 IQR 42.9-59.2 mL/m2; p=0.101; no AF baseline 43.5 mL/m2 IQR 34.2-60.5 mL/m2 f-u 42.0 mL/m2 IQR 32.0-46.2 mL/m2; p=0.012). As regards right sections, the most relevant positive remodeling was obtained in patients with functional MR with a baseline poorer RV function and more severe RA and RV dilation. (Table 1) Conclusion: At mid-term follow-up after PMVR, a positive cardiac remodeling is detected in atrial and ventricular chambers also involving the right sections. To deliver a tailored intervention, MR mechanism and history of AF should be considered in view of the impact on remodeling process. Baseline, median [IQR] Follow-up, median [IQR] p val PRIMARY MR (N=11) LVEDD (mm) 50.0 [49.0-59.0] 46.0 [42.0–57.0] .005 LVESD (mm) 42.0 [37.0-49.0] 40.0 [38.0–45.0] .284 RWT 0.32 [0.29-0.38] 0.35 [0.31–0.38] .424 iLVM (gr/m 2 ) 111.1 [95.1-142.9] 79.2 [52.3–103.3] .005 2D-iLVEDV (ml/m 2 ) 61.4 [45.4-77.7] 48.9 [40.5-61.6] .003 2D-iLVESV (ml/m 2 ) 25.2 [21.2-39.8] 20.4 [14.75–30.8] .182 2D-LVEF (%) 59.1 [50.7-61.5] 61.5 [50.0–63.9] .477 LV-S' (TDI) (cm/s) 8.0 [7.5-9.5] 8.0 [6.0–10.0] .157 2D-iLAV (ml/m 2 ) 42.3 [34.2-51.7] 36.3 [29.6–47.0] .005 PALS (%) 12.0 [4.0-17.0] 21.0 [19.0–22.0] .109 TR Vmax (m/s) 3.0 [2.5-3.1] 2.0 [1.8–2.5] .005 EPSPAP (mmHg) 40.0 [35.0-50.0] 20.0 [15.0–25.0] .003 Basal RVD (mm) 35.0 [31.0-40.0] 32.0 [29.0–37.0] .058 Mid-cavity RVD (mm) 27.0 [25.0-34.0] 26.0 [23.0–31.0] .010 Longitudinal RVD (mm) 59.0 [52.0-68.0] 53.0 [47.0–60.0] .005 RA Area (cm 2 ) 18.0 [15.0-23.0] 14.0 [13.0–16.0] .035 FAC (%) 37.0 [35.0-44.0] 45.0 [43.0–47.0] .016 TAPSE (mm) 20.0 [17.0-24.0] 20.0 [18.0-26.0] .072 RV S' (TDI) (cm/s) 9.0 [8.0-13.7] 9.0 [8.7–13.0] .581 RV-FWLS (%) -21.0 [-15.1–-23.0] - 23.0 [-24.0 – -22.0] .141 Table 1 baseline and follow-up echocardiography assessment Baseline, median [IQR] Follow-up, median [IQR] p val secondARY MR (N=13) LVEDD (mm) 60.0 [53.0-65.0] 60.0 [50.0–63.0] .058 LVESD (mm) 45.0 [40.5-52.0] 47.0 [41.5–50.0] .833 RWT 0.31 [0.26-0.37] 0.33 [0.25–0.38] .347 iLVM (gr/m 2 ) 116.9 [96.2-136.4] 100.8 [58.2–141.6] .239 2D-iLVEDV (ml/m 2 ) 76.4 [60.5-94.9] 59.4 [44.8–91.2] .002 2D-iLVESV (ml/m 2 ) 50.2 [35.5-67.1] 31.9 [23.1–53.9] .004 2D-LVEF (%) 42.4 [35.9-48.2] 46.3 [38.5–49.6] .433 LV-S' (TDI) (cm/s) 6.5 [5.3-8.0] 8.0 [7.0–9.0] .105 2D-iLAV (ml/m 2 ) 53.8 [45.2-62.6] 50.7 [43.6–60.1] .213 PALS (%) 10.0 [5.0-17.0] 6.8 [5.2–17.5] .500 TR Vmax (m/s) 2.9 [2.5-3.2] 2.4 [2.0–2.7] .056 EPSPAP (mmHg) 42.5 [31.3-53.8] 30.0 [20.0–35.0] .005 Basal RVD (mm) 39.0 [37.0-43.0] 34.0 [32.0–38.5] .004 Mid-cavity RVD (mm) 30.0 [26.0-35.0] 28.0 [21.5–29.5] .016 Longitudinal RVD (mm) 65.0 [60.5-71.0] 60.0 [57.5–63.0] .012 RA Area (cm 2 ) 21.0 [17.5-25.0] 18.0 [15.5–22.5] .040 FAC (%) 34.0 [30.0-37.0] 42.0 [34.0–48.5] .009 TAPSE (mm) 14.0 [13.0-14.0] 17.0 [14.5–19.0] .005 RV S' (TDI) (cm/s) 7.0 [6.0-10.8] 9.5 [8.3–12.8] .068 RV-FWLS (%) -15.0 [-9.9 – 19.8] - 19.5 [-16.0 – -22.5] .021